Removal of cytostatic drugs from aquatic environment: A review - Giannis, Apostolos (2016)
Cytostatic drugs have been widely used for chemotherapy for decades. However, many of them have been categorized as carcinogenic, mutagenic and teratogenic compounds, triggering widespread concerns about their occupational exposure and ecotoxicological risks to the environment. This review focuses on trace presence, fate and ecotoxicity of various cytostatic compounds in the environment, with an emphasis on the major sources contributing to their environmental concentrations. Past records have documented findings mainly on hospital effluents though little effort has been directed to household discharges. There is also a lack in physico-chemical data for forecasting the chemodynamics of cytostatics in natural waters along with its human metabolites and environmental transformation products. In this light, obtaining comprehensive ecotoxicity data is becoming pressingly crucial to determine their actual impacts on the ecosystem. Literature review also reveals urinary excretion as a major contributor to various cytostatic residues appeared in the water cycle. As such, engaging urine source-separation as a part of control strategy holds a rosy prospect of addressing the “emerging” contamination issue. State-of-the-art treatment technologies should be incorporated to further remove cytostatic residues from the source-separating urine stream. The benefits, limitations and trends of development in this domain are covered for membrane bio-reactor, reverse/forward osmosis and advanced oxidation processes. Despite the respective seeming advantages of source separation and treatment technology, a combined strategy may cost-effectively prevent the cytostatic residues from seeping into the environment. However, the combination calls for further evaluation on the associated technological, social-economic and administrative issues at hand.